Dlx regulation in zebrafish brain development via I56iI56ii and I12aI12b - Burton, Lindsay (University of Ottawa (Canada), 2008)
Dlx genes are involved in the formation of the forebrain, branchial arches, sensory organs, and limbs. In the forebrain, Dlx genes are expressed in restricted domains in the telencephalon and diencephalon. The telencephalon is one of the most complex structures in the vertebrate central nervous system, but despite variable morphologies of the adult telencephalon, the patterning and basic organization is conserved amongst vertebrates. Cis-acting regulatory sequences (CREs) that contribute to Dlx expression in the telencephalon were previously identified in the intergenic region between Dlx5 and Dlx6 (I56i and I56ii), between Dlx1 and Dlx2 (I12b), and upstream of Dlx1 (URE2) in zebrafish, mouse, and human. I hypothesize that these CREs contribute to defining distinct subtypes of interneurons during forebrain development. In this study, we have investigated the differential activity of intergenic CREs in the developing zebrafish brain using the established transgenic lines Tg(6kb-dlx1a/dlx2a: EGFP) and Tg(1.4kb-dlx5a/dlx6a:EGFP) in which the green fluorescent protein gene (GFP) was used as a reporter whose expression was controlled by dlx CREs. The two intergenic fragments target reporter transgenes with overlapping patterns of expression in the telencephalon but also show differential activity in the dorsal region of the brain at the level of the pallium. These results suggest that the dlx1a/2a CREs are involved in dlx regulation in a set of cells occupying the subpallium, whereas the dlx5a/6a CREs are involved in dlx regulation in a set of cells that migrate out of the subpallium and travel in a ventral to dorsal manner to occupy the pallium. Co-localization of GFP with GAD65/67 and with molecular markers of the interneuron subtype, calretinin, indicates that the dlx CREs target the reporter constructs to GABAergic interneurons, with at least one subtype expressing calretinin. Results from this study reflect a dynamic regulation of dlx gene expression in the developing zebrafish forebrain through several regulatory elements with distinct and overlapping functions.
Keywords: Biology, Molecular.; Biology, Neuroscience.